Graph classes a survey - Brandstädt, Andreas 1949-; Le, Van Bang 1959-; Spinrad, Jeremy P. (SIAM monographs on discrete mathematics and applications, 1999)
This well-organized reference is a definitive encyclopedia for the literature on graph classes. It contains a survey of more than 200 classes of graphs, organized by types of properties used to define and characterize the classes, citing key theorems and literature references for each. The authors state results without proof, providing readers with easy access to far more key theorems than are commonly found in other mathematical texts. Interconnections between graph classes are also provided to make the book useful to a variety of readers